Overlap of periodic paralysis and paramyotonia congenita caused by SCN4A gene mutations two family reports and literature review - Huang, Shan (Channels (Austin), 2019)
Objective: To verify the diagnosis of channelopathies in two families and explore the mechanism of the overlap between periodic paralysis (PP) and paramyotonia congenita (PMC). Methods: We have studied two cases with overlapping symptoms of episodic weakness and stiffness in our clinical center using a series of assessment including detailed medical history, careful physical examination, laboratory analyses, muscle biopsy, electrophysiological evaluation, and genetic analysis. Results: The first proband and part of his family with the overlap of PMC and hyperkalemic periodic paralysis (HyperPP) has been identified as c.2111C > T (T704M) substitution of the gene SCN4A. The second proband and part of his family with the overlap of PMC and hypokalemic periodic paralysis type 2 (HypoPP2) has been identified as c.4343G > A (R1448H) substitution of the gene SCN4A. In addition, one member of the second family with overlapping symptoms has been identified as a novel mutation c.2111C > T without the mutation c.4343G > A. Conclusions: SCN4A gene mutations can cause the overlap of PMC and PP (especially the HypoPP2). The clinical symptoms of episodic weakness and stiffness could happen at a different time or temperature. Based on diagnosis assessments such as medical history and muscle biopsy, further evaluations on long-time exercise test, genetic analysis, and patch clamp electrophysiology test need to be done in order to verify the specific subtype of channelopathies. Furthermore, the improvement of one member in the pregnancy period can be used as a reference for the other female in the child-bearing period with T704M.